Development of Process Oriented Guided Inquiry Learning Worksheets (POGIL) to Improve Critical Thinking Skills and Science Process Skills - Fajarotul Hidayah; Paidi; Fadli Robby Al-Farisi; Nida Husna (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the feasibility of POGIL-based LKPD to empower students' critical thinking skills and Science Process Skills. The type of research used is research and development with research procedures using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). This research is limited to the feasibility test of POGIL-based LKPD at the development stage. The assessment of the results of the validity test and the practicality test of the questionnaire is interpreted on a Likert scale. Based on data analysis, the following results were obtained: product validity test in the form of POGIL-based LKPD by media experts obtained an average of 87% with very feasible criteria and 78.3% by material experts with feasible criteria. Practicality tests conducted by Biology teachers get an average of 84.35% and students 85% with very decent criteria.